Implementation Of The Inter Tk Package, Sub-Process And Os In The Network Management Application Development With Python Programming Language - Muhammad Guntur Akbar; Harry Witriyono; Yovi Apridiyansyah; Dedy Abdullah (Jurnal Komputer, Informasi dan Teknologi, 2023)
The development of technology is currently running very rapidly, especially in the field of computer networks that make it possible to connect all people from various places. The need for information triggers the rapid development of network infrastructure technology by several vendors or brands. The need for network infrastructure is of course inseparable from the large number of users who use the internet service, causing new problems because the number of users is not proportional to the number of technicians available. For general users, they can wait for the handling schedule from the technician, while for agencies that need a network to complete their work, they don't have that time. To overcome this, you can use a special program to check the network regularly where everyone can use it so that it can reduce free customer service at network providers. One programming language that can be used open source for the development of these applications is python. Python is a multipurpose interpretive programming language with a design philosophy that focuses on code readability. Python programming is still rarely used because it still uses the terminal as the main access where the user has to type certain code to execute the desired result, such as the Command Prompt Windows (CMD) program. The use of python-based applications can be made more comfortable for users by using a GUI (Graphical user interface) display using the TKInter library, which is a standard Python package for creating GUI displays. Tkinter has an interface to the Tk toolkit that can work as an object-oriented layer on top of Tk. Tkinter has many components that can be used to create user-friendly interfaces. Apart from Tkinter, the application uses a subprocess and os library which functions to access the terminal and execute certain comments in the terminal. The built application has functions for pinging, nslookup, ipconfig, network info, active connection and network processes. Ping and Nslookup require data to be entered in text input on the same line, for ping you can input the IP address of the intended network or website address (requires internet connection) while nslookup can be filled in with the website address.